Clinical ethics at the crossroads of genetic and reproductive technologies - Hostiuc, Sorin (Elsevier, Academic Press, an Imprint of Elsevier, 2023)
The Human Genome Project has triggered a technological revolution that has influenced nearly every field of medicine, including reproductive medicine, obstetrics, gynecology, andrology, prenatal genetic testing, and gene therapy. This second edition of Clinical Ethics at the Crossroads of Genetic and Reproductive Technologies offers a thorough, timely discussion of ethical issues raised by the latest genetic and genomic technologies applied in human reproductive and prenatal medicine, providing practical recommendations, guidelines, and algorithms to support ethical clinical practice. Here, international experts consider the ethics of technologies from preconception carrier screening to genetic engineering, CRISPR gene editing, mitochondrial gene replacement therapy, sex selection, predictive testing, secondary findings, embryo reduction, and the moral status of the embryo, genetic enhancement, and the sharing of genetic data. Throughout the book, contributors adopt a global, holistic perspective on applied challenges and the moral questions around the implementation of genetic reproductive technologies. The book is an ideal resource for practitioners, regulators, lawmakers, clinical researchers, genetic counselors, and graduate and medical students.This fully updated second edition examines new developments in the field, tackling ethical aspects of organoid development, recent advances in pharmacogenomics, direct-to-consumer genetic testing, and genetic engineering.